INTELLIGENT OFFICE CHAIR USING RASPBERRY PI - Shivprasad, Lingampally; Krishna, I. Raghava; Devendher, K.; Sandyarani, B. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
In offices related to software, working professors in schools, colleges, etc,people sit for longer hours. Due to this they suffer with many health issues like overweight, joint pain, back pain, etc. this has become an increasing problem now a days. To overcome this, the project is designed which is called as “Intelligent Office Chair”. This chair instructs the person sitting on the chair if he/she sit for long duration. Also this chair height can be adjusted up or down through the app. To prove the concept practically, a proto type module is designed and developed using Raspberry pi, Using the IP address we can adjust the height, buzzer to remind the person that he/she is sitting more thanthe normal time so that they can take a break for some time duration. Ultrasonic sensor is also used to instruct the person, if he/she isn’t sitting properly. The chair measures different parameters designed through sensors like ultrasonic sensor for distance measurement of the posture of the person, IR sensor for obstacle detection etc. This project isdesigned with most demanding technology that is Raspberry pi. Preliminary results show that the Chair combined with case-study smart phone application can accurately detect the parameters and indicates or informs through the output equipment Vibrator etc. In this project IP address plays a major role , with the help of that we built this project. With the help of Relay we can sense the Vibration